New wound dressing based on chitosan/hyaluronan biopolymers - Abdel-Rahman, Rasha (Univerzita Pardubice, 2016)
This dissertation is organized as follows. Chapter 1 presents an in-depth literature review. Chapter 2 presents the isolation and characterization of chitin and chitosan from Brazilian Atlantic Coast. Chapter 3 focuses on the preparation and characterization of new wound dressing based on hyaluronan and chitosan with using non-woven fabric. Chapter 4 focuses on the conclusion and future work.
Nové kryty ran založené na chitosanu a hyaluronanu
Keywords: chitin; chitosan; hyaluronan; rány; netkané textilie; Polysaccharides; wounds; chitosan; hyaluronan; diabetic and non-diabetic case